Colour Tribulations: A Mothering-ArtAdemic in a Pandemic - Brady Nelson, Meaghan (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Using personal narrative as a feminist approach to producing knowledge, I describe how living in a pandemic creates the ultimate experience to conduct arts-based research on gender inequality for artists, educators, and professionals as well as the effects the process of artmaking can have on grief, depression, and anxiety. From the onset of the COVID-19 pandemic, I experienced the death of two family members. With the stay-safer-at-home order, I was thrust into finding a way to balance the roles of caring for multiple generations of my family, quickly moving to teaching online, attempting to teach and care for my daughters, and dealing with the deaths of two loved ones. The order of social distancing caused my personal grief to remain in a fog. As a Mothering-ArtAdemic (Nelson and Combe), I needed to find a way to successfully mother, create, and teach in order to remain strong and heal for myself, my family, and my students. After tending to my stay-safer-at-home duties as a Mothering-ArtAdemic, I empowered myself to paint every day. This series of abstract paintings is called Colour Tribulations, as I played with colour to fight off the anxiety, troubles, difficulties, and constant uncertainty of living in a pandemic. Each painting represents an attempt to find peace as well as a sense of safety and calm in the midst of COVID-19 chaos. The paintings conceptually work through the multitude of stresses and anxieties that accompany mothering and teaching in the midst of a pandemic and transform them into meditation, colour, and forms of art therapy.